2018
DOI: 10.18844/ijlt.v10i4.3634
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the improvised logic gates simulator in basic digital electronics instruction

Abstract: This study was conducted at Caraga State University – Cabadbaran campus (CSUCC) particularly in the College of Industrial Technology and Teacher Education (CITTE), Electronics Technology Area. It was aimed at determining the effectiveness of the Improvised Logic Gates Simulator as an instructional device in basic digital electronics instruction to enhance the teaching-learning process. Effectiveness of the simulator was evaluated using the experimental method of research through the administration of pre-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
1
0
0
Order By: Relevance
“…In terms of perception of which of these can be e -commerce, this result was obtained that 23.6% know what this is and based on this it can be concluded that less than a quarter of users know what e -commerce really is. This result corroborates to that of Arante [23] and Pineida [24].…”
Section: Resultssupporting
confidence: 90%
“…In terms of perception of which of these can be e -commerce, this result was obtained that 23.6% know what this is and based on this it can be concluded that less than a quarter of users know what e -commerce really is. This result corroborates to that of Arante [23] and Pineida [24].…”
Section: Resultssupporting
confidence: 90%